Acceptance and practices on new paddy seed variety among farmers in MADA granary area - Nazuri, Nur Shuhamin; Man, Norsida (Mediterranean Center of Social and Educational Research, 2016)
This paper employed survey data to identify farmers’ acceptance and practices on new paddy seed variety in MADA granary area in Kedah Malaysia. 250 of respondents who are paddy farmers in four districts area (Perlis, Jitra, Pendang and Kota Sarang Semut) were involved in this interview. The objective of the study was to obtain farmers’ acceptance and practices on new paddy seed variety. The results show that socio- demographic of respondents in MADA area represents 93.2% of respondents are male and the rest of 6.8% are female farmers. The most predominant age group of the respondents between 51 to 60 years old which are 37.6%. For the marital status of the respondents, there were 64.4% are married, 15.6% are single and 20% are widow and widower. 29.6% respondents went to primary schools while about 50.8% went to secondary schools. Meanwhile, 12.4% had college/university education and only 7.2% did not get any formal education. The overall mean for perception level toward advantage and disadvantage rice variety selected is 3.902 considered as a high level of perception. Meanwhile, for chi-square analysis, it illustrates a significant different on age and years of involvement towards a level of practices on using new paddy seed variety.